FENOMENA ANEMIA ZAT BESI PADA REMAJA DI KECAMATAN ANDOOLO UTAMA, KABUPATEN KONAWE SELATAN - Yunita, Dewi; Putri , Eka Novia Syah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Iron deficiency anemia is a major public health issue in South Konawe Regency. This condition is characterized by low hemoglobin levels in the blood, primarily caused by insufficient iron intake. Based on examinations, 144 adolescents were diagnosed with mild anemia, while two cases involved severe anemia. Common symptoms reported include fatigue, dizziness, and difficulty concentrating, all linked to low hemoglobin levels. The data for this study were collected through interviews and document analysis. The findings indicate that the primary causes of anemia among adolescents in Andoolo Utama include poor dietary habits, a lack of awareness about the importance of balanced nutrition, and practices such as frequently skipping breakfast. To prevent anemia, routine educational sessions on healthy eating habits are conducted in schools, along with providing information to parents to ensure their children consume iron-rich foods such as red meat, liver, and green vegetables. Additionally, the distribution of iron supplementation tablets (TTD) to adolescent girls is considered essential to improve hemoglobin levels, which often decrease due to menstruation.